2020
DOI: 10.1111/dth.13560
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis in patients with frontal fibrosing alopecia: An international multi‐center study

Abstract: Frontal fibrosing alopecia (FFA) mainly affects the anterior hairline and eyebrows and its etiology and associated factors remain obscure. The aim of this study was to evaluate the allergic contact dermatitis with patch test in patients with FFA. In this prospective study, 20 patients with FFA and 24 age and sex‐matched healthy individuals were evaluated with patch testing. Diagnosis was made histologically, clinically and based on dermoscopic findings. Demographic data, age of onset, disease duration and FFA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…This remains an enigma, thus provided the triggers are identified, patients would have an opportunity to actively prevent the origination and/or progression of the disease.Prior research found that, among patients with FFA, cosmetics use (eg, sunscreens) is pronounced 2-4 and patch-test reactions are frequent. 2,[5][6][7] We found frequent sensitization to allergens, such as BS (22%), gallates (16.6%), propolis (16.6%), and limonene hydroperoxides (13.8%) in 36 patients with FFA. 1 Of interest, in some patients, reactions to BS, gallates, and propolis seemed to be concomitant, 1 suggesting a peculiar allergenic profile.…”
mentioning
confidence: 83%
“…This remains an enigma, thus provided the triggers are identified, patients would have an opportunity to actively prevent the origination and/or progression of the disease.Prior research found that, among patients with FFA, cosmetics use (eg, sunscreens) is pronounced 2-4 and patch-test reactions are frequent. 2,[5][6][7] We found frequent sensitization to allergens, such as BS (22%), gallates (16.6%), propolis (16.6%), and limonene hydroperoxides (13.8%) in 36 patients with FFA. 1 Of interest, in some patients, reactions to BS, gallates, and propolis seemed to be concomitant, 1 suggesting a peculiar allergenic profile.…”
mentioning
confidence: 83%
“…A higher frequency of positive patch test in FFA patients, mainly for fragrances [ 93 ], benzyl salicylate [ 102 ], cobalt, nickel, and potassium dichromate [ 103 ], have been found in different studies, although others do not suggest any association of FFA with photoallergy to several cosmetic-related substances (including chemical sunscreen filters) or titanium dioxide [ 100 , 104 ]. Moreover, the positive patch test may be a consequence of increased exposure to these substances.…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…The most common allergens encountered in the FFA group were cobalt chloride hexahydrate 35%, nickel sulfate hexahydrate 25%, and potassium dichromate 15%. 7 In our study, 83.3% of cases and 55.5% of controls had at least one positive allergen.…”
mentioning
confidence: 43%